2020
DOI: 10.3390/s20061718
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Measuring System for Electricity Quality Monitoring within the SMART Street Lighting Test Polygon: Pilot Study on Adaptive Current Control Strategy for Three-Phase Shunt Active Power Filters

Abstract: This study focuses on the design of a measuring system for monitoring the power quality within the SMART street lighting test polygon at university campuses with relation to testing an adaptive current control strategy for three-phase shunt active power filters. Unlike conventional street lighting, SMART elements are powered 24/7. Due to the electronic character of the power part of such mass appliances, there are increased problems with the power quality of the electric energy. Compared to the current concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 65 publications
(72 reference statements)
0
31
0
1
Order By: Relevance
“…where idiffj denotes the phase j inter-circulating current that circulates between the upper and lower legs and is expressed as below: As discussed in [7], the MMC operates according to the following equations:…”
Section: Model Of the Modular Multilevel Converter (Mmc)mentioning
confidence: 99%
See 2 more Smart Citations
“…where idiffj denotes the phase j inter-circulating current that circulates between the upper and lower legs and is expressed as below: As discussed in [7], the MMC operates according to the following equations:…”
Section: Model Of the Modular Multilevel Converter (Mmc)mentioning
confidence: 99%
“…where ej denotes the inner emf produced in phase a and is given as follows: As discussed in [7], the MMC operates according to the following equations:…”
Section: Model Of the Modular Multilevel Converter (Mmc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results were delivered by choosing a real case study of STCOMET, a commercial electronic board widely used for remote energy metering purposes, and the paper has verified the possibility to implement PQ metrics in it. The authors of [ 18 ] designed an intelligent street lighting PQ monitoring system to test the adaptive current control strategy, in which a commercial measurement system from National Instruments (NI) cDAQ-9185 was used. As a result, they observed that the THD decreased by 19% on average.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the frequency of voltage waveforms in power supply networks is one of the most important parameters from the point of view of, e.g., power quality measurements [1,2] and power network protection automation devices, especially those occurring in inverters used in the photovoltaic industry [3][4][5]. In the first industry, incorrect estimation of the fundamental frequency of the waveform results in a so-called spectrum leakage, and consequently, in an increased uncertainty of measurement of spectral parameters such as harmonics and interharmonics.…”
Section: Introductionmentioning
confidence: 99%